Role of Instructional Resources in Enhancing Teaching and Learning in Nigerian Schools - Zhenseh, Abershi Japhet; Umar, Abdulrahman (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
Instructional resources are essential tools and materials that facilitate effective teaching and learning in schools. They bridge the gap between theoretical concepts and practical understanding, enhance student engagement, and improve learning outcomes. In Nigerian schools, the provision and utilization of instructional resources remain uneven, with urban and well-funded schools often better equipped than rural or under-resourced institutions. This study examines the role of instructional resources in enhancing teaching and learning in Nigerian schools, highlighting their impact on concept comprehension, active learning, academic performance, teacher efficiency, inclusion of diverse learners, and skill development. Using a position paper methodology, the study draws on secondary data from academic literature, government policy documents, and international best practices to critically analyze the availability, utilization, and challenges associated with instructional resources in Nigeria. Findings reveal that adequate and properly utilized instructional resources significantly improve teaching effectiveness, facilitate curriculum implementation, motivate learners, and promote practical skill acquisition. Conversely, limited or poorly managed resources contribute to poor academic performance, disengaged learners, and reduced teaching efficiency. The study underscores the need for strategic investment in instructional materials, teacher training, and resource management to ensure that Nigerian schools can deliver quality education and achieve national educational goals.